The study of hydroxyoximes and hydroxamic acids supported on macroporous resins and their use in the rapid seperation of metals - Hemmes, Marlene (Rhodes University, Faculty of Science, Department of Chemistry, 1979)
Introduction: The macroporous Amberlite XAD resins were coated with LIX-64N and examined for the rate of uptake of copper . XAD-7 was by far the best support and gave a satisfactory rate of uptake up to loadings of 60% (w/w). The specific surface area of XAD-7 was measured by the adsorption of methylene blue from aqueous solution. The area of the wetted resin was five times less than that of the dry resin. LIX-65N was purified and the anti isomer characterised using spectroscopic techniques . The rate of uptake of copper was not improved by use of purified LIX-65N or by addition of LIX-63. XAD-7 coated with LIX-65N was used in columns. Elution curves for copper showed negligible tailing, and rapid separations of copper from iron (111), nickel, cobalt and magnesium by selective absorption were achieved. Copper was concentrated from very dilute solution at a flow rate of 50 ml min -1 ,and a 99% recovery was obtained. The method was applied to the rapid determination of copper in brass and bronze. A series of long-chain hydroxamic acids were synthesised and tested for suitability as stationary phase on XAD-7. Oleohydroxamic acid and naphthenohydroxamic acid were the most promising. The r ate of uptake of copper was reduced by the use of nonylphenol or amyl alcohol as a diluent. The capacities for copper of the hydroxamic acids were less when supported on XAD-7 than when used as liquid ionexchangers. The distribution coefficients of cobalt, nickel, zinc, lead, vanadium, uranium, iron (111) and copper were measured as a function of pH. XAD-7 coated with oleohydroxamic acid was used in columns for the rapid separation of iron (111) from copper and of copper from nickel, cobalt, lead and zinc. Copper was concentrated from very dilute solution at a flow rate of 45 ml min -1 and a 100,8% recovery was obtained. Copper was successfully separated from nickel by selective elution. The elution curves obtained show negligible tailing. The resin loaded with oleohydroxamic acid lost capacity due to chemical instability. Naphthenohydroxamic acid supported on XAD-7 was not suitable for use in columns, because it was physically unstable.
Keywords: Chromatographic analysis; Separation (Technology); Metal ions; Solvent extraction; Extraction (Chemistry); Oximes; Metals -- Analysis